Konstruktion av skjutrigg till 155mm - L52 - Klasson, Gustav; Ljungberg, Linus (My University, 2025)
This project focuses on the design of a firing rig intended for the test firing of highly loaded artillery components such as barrels, breech blocks, muzzle brakes, and recoil dampers. Initially an information-gathering phase was conducted by collecting requirements and needs from engineers at the company with experience in previous design projects. Their input from them formed the foundation of the work. The company aims to achieve a more efficient testing process by using a stationary firing rig that enables test firing of the recoiling components in complete assemblies. With such a rig, it becomes easy to mount heavily loaded components onto the rig, conduct test firings, and remove them for inspection. This setup makes it possible to stock pre-tested components that can be used by the production department during the manufacturing of artillery systems. The goal of the project was to use multiple simulations as decision support to arrive at a final concept that meets all requirements of the rig. Based on the project background, the objective was to design a stationary firing rig with a focus on structural strength to withstand the forces generated by the firing impulse. The rig should provide a good working height and accessibility, creating a practical and safe working environment for easy assembly and disassembly during test firing. The development of additional equipment for the rig, such as cradle extensions, split yokes, and foldable yoke supports, is not covered in this report. The result of the project consists of a solution for a firing rig constructed from rectangular beam profiles with dimensions of 250x250 mm and a wall thickness of 15 mm. The rig is equipped with square and rectangular plates to allow stable and secure attachment between the firing rig and the track plate, specifically adapted to the dimensions of the track plate. A plate is welded on top of the firing rig with an interface adapted to the trunnion fork and bearing. The rig is fixed to the track plate using clamping brackets and a mechanical stop. A structural strength analysis using Ansys confirmed that the final design meets the requirements to withstand the stresses encountered during test firing, ensuring long service life, safety, and good ergonomics during firing.